P402 Incidence and outcomes of herpes zoster in the ozanimod phase, 3 ulcerative colitis and relapsing multiple sclerosis clinical program. (21st January 2022) - Siegmund, B; Melmed, G Y; Irving, P M; Pai, A; Patel, A; Sheffield, J K; Caldera, F; Cree, B A C; Dubinsky, M C
Abstract: Background: Patients with ulcerative colitis (UC) and patients with multiple sclerosis (MS) have an elevated risk of developing herpes zoster (HZ), caused by reactivation of latent varicella zoster virus (VZV). Increased incidence of HZ has been reported with sphingosine, 1-phosphatase (S1P) receptor modulators. This analysis examined the number of patients who failed screening due to a lack of demonstrated VZV immunity and the incidence of HZ from completed phase, 3 ozanimod clinical trials. Methods: Safety results were included from True North (52-week trial) in patients with UC, and SUNBEAM (12-month trial), and RADIANCE (24-month trial) in patients with MS. All patients were required to have had a positive VZV IgG antibody status or completed VZV vaccination ≥30 days prior to randomization based on known effects of S1P modulators. Patients with a negative VZV antibody titer could choose to receive the VZV vaccination to qualify for the trial. Number of pre-screen failures because of lack of demonstrated immunity, occurrence of HZ, and association between HZ cases and lymphopenia were analyzed. Results: Of, 1831 patients with UC screened for VZV immunity, 104 (5.7%) failed screening due to lack of documentation of VZV antibody or VZV vaccination ≥30 days before randomization;, 22% (23/104) subsequently received varicella vaccination and were rescreened and enrolled. Of, 3332 MS patients tested for VZV immunity, 309 (9.3%) tested negative and, 32% (98/309) of these patients were vaccinated prior to randomization. In the UC and MS trials, the incidence of HZ cases was low in ozanimod-treated patients (8 cases [1.0%] and, 5 cases [0.6%], respectively; Table, 1). All cases were distributed across a single dermatome, did not result in a complication of HZ, and were treated with oral antivirals while patients remained on ozanimod. None of the patients discontinued ozanimod because of HZ and none of the HZ cases were associated with grade, 4 lymphopenia (defined as an absolute lymphocyte count <0.2 x, 10 9 /L). Conclusion: In the ozanimod phase, 3 UC and MS trials, 5%–10% of patients screened did not have demonstrated VZV immunity;, 22%–32% of these patients received varicella vaccination, were rescreened and enrolled. The overall HZ incidence in clinical trials was low (≤1% of patients), all cases were distributed across a single dermatome, and no serious or complicated cases occurred in ozanimod-treated patients with VZV immunity. Additional studies are warranted to evaluate the incidence of HZ in clinical practice.